![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
4个回答
展开全部
由题意:3*(x-2)+1=x-(2x-i)
即 3x-5=i-x
那么 4x=5+i
即x=5/4 +i/4
即 3x-5=i-x
那么 4x=5+i
即x=5/4 +i/4
展开全部
由题意3(X-2)+1=x-(2x-i)
3x-5=i-x
∴4x=5+i
∴
x=5/4 +i/4
3x-5=i-x
∴4x=5+i
∴
x=5/4 +i/4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
3(x-2)+1=x-(2x-i)
3x-5=-x+i
4x=5+i
x=(5+i)/4
3x-5=-x+i
4x=5+i
x=(5+i)/4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
由题意:3*(x-2)+1=x-(2x-i)
即 3x-5=i-x
那么 4x=5+i
即x=5/4 +i/4
即 3x-5=i-x
那么 4x=5+i
即x=5/4 +i/4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询